Sugammadex for the treatment of rocuronium‐induced anaphylaxis. Issue 1 (6th February 2014) - Williams, Stuart; Nesvadba, David Stephen; Bathgate, Gordon
Summary: The treatment of rocuronium induced anaphylaxis with sugammadex as an adjunct to standard resuscitation protocols has been reported in the literature. We describe a further case to add to the growing evidence base and discuss some of the pertinent issues.